Smile [book club bag] - Telgemeier, Raina (Smile ;, 2010)
The author relates, in graphic form, her experiences after she injured her two front teeth and had to have surgeries and wear embarrassing braces and headgear, all while also dealing with the trials and tribulations of middle school.